PENGARUH IMPLEMENTASI ERP TERHADAP PRODUCT DIFFRENTIATION DAN COST LEADERSHIP DALAM MENINGKATKAN KINERJA PERUSAHAAN (Studi Kasus Manufaktur Jawa Timur) - Zeplin Jiwa Husada Tarigan (Institute of Research and Community Outreach - Petra Christian University, 2009)
The study presented in this paper examines the adoption ERP practices a systematic explanation of the relationships marketing strategy, and enterprise performance. By examining ERP in relation to organization strategy, the study seeks to advance the understanding of ERP in a broader context. It also resolves some controversies that appear in the literature concerning the relationship between ERP and differentiation strategies and low cost strategies as well as quality and innovation performance. The empirical data for this study was drawn from a survey of 53 enterprises from East Java. The analysis was conducted using structural equation modeling (SEM) with software Amos 16 start technique by examining two competing models that represent full. The findings indicate that adoption ERP is positively and significantly related to low cost strategy and not significantly to differentiation strategy. The implication is that ERP needs to be complemented by other resources to more effectively realize the strategy in achieving a high level of performance.